PROBLEMS AND THEIR SOLUTIONS IN INSURANCE OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Saidullaeva Saodat Abdumajitovna; Nurullaeva Shakhnoza Tokhtasinovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article presents ideas and opinions about the problems and their solutions in the insurance of small business and private entrepreneurship.